Russian Language Development Assessment as a Standardized Technique for Assessing Communicative Function in Children Aged 3-9 Years - Prikhoda N.A (Moscow State University of Psychology and Education, 2016)
The article describes the Russian Language Development Assessment, a standardized individual diagnostic tool for children aged from 3 to 9 that helps to assess the following components of a child's communicative function: passive vocabulary, expressive vocabulary, knowledge of semantic constructs with logical, temporal and spatial relations, passive perception and active use of syntactic and morphological features of words in a sentence, active and passive phonological awareness, active and passive knowledge of syntactic structures and categories. The article provides descriptions of content and diagnostic procedures for all 7 subtests included in the assessment (Passive Vocabulary, Active Vocabulary, Linguistic Operators, Sentence structure, Word Structure, Phonology, Sentence Repetition). Basing on the data collected in the study that involved 86 first- graders of a Moscow school, the article analyzes the internal consistency and construct validity of each subtest of the technique. It concludes that the Russian Language Development Assessment technique can be of much use both in terms of diagnostic purposes and in supporting children with ASD taking into account the lack of standardized tools for language and speech development assessment in Russian and the importance of this measure in general.